Highly Thermally Conductive Liquid Crystalline Epoxy Resin Vitrimers with Reconfigurable, Shape‐Memory, Photo‐Thermal, and Closed‐Loop Recycling Performance - Fengyuan Zhang; Junliang Zhang; Kuan Zhang; Xiao Zhong; Mukun He; Hua Qiu; Junwei Gu (Advanced Science)
Abstract The low thermal conductivity, poor toughness, and non‐reprocessability of thermosetting epoxy resins severely restrict their applications and sustainable development in flexible electronics. Herein, liquid crystalline epoxy (LCE) and dynamic ester and disulfide bonds are introduced into the cured network of bisphenol A epoxy resin (E‐51) to construct highly thermally conductive flexible liquid crystalline epoxy resin (LCER) vitrimers. LCER vitrimers demonstrate adjustable mechanical properties by varying the ratio of LCE to E‐51, allowing it to transition from soft to strong. Typically, a 75 mol% LCE to 25 mol% E‐51 ratio results in an in‐plane thermal conductivity (λ) of 1.27 W m−1 K−1, over double that of pure E‐51 vitrimer (0.61 W m−1 K−1). The tensile strength and toughness increase 2.88 folds to 14.1 MPa and 2.45 folds to 20.1 MJ m−3, respectively. Besides, liquid crystalline phase transition and dynamic covalent bonds enable triple shape memory and three‐dimensional shape reconstruction. After four reprocessing cycles, λ and tensile strength remain at 94% and 72%, respectively. Integrating carbon nanotubes (CNTs) imparts photo‐thermal effect and enables “on” and “off” switch under near‐infrared light to LCER vitrimer. Furthermore, the CNTs/LCER vitrimer displays light‐induced actuation, self‐repairing, and self‐welding besides the closed‐loop recycling and rapid degradation performance.